Management of elderly patients with esophageal squamous cell cancer. (30th April 2022) - Hamamoto, Yasuo; Murakami, Kentaro; Kato, Ken; Kitagawa, Yuko
Abstract: This review focuses on the treatment about elderly esophageal cancer to clarify the current situation regarding our clinical question. Although there are several reviews about elderly esophageal cancer treatment, there are fundamental differences between Japan and the rest of the world. Two main differences are raised: histological differences and treatment strategies for resectable patients. We overview each status according to following clinical questions. First, there are no established evaluation criteria for frail. Second, selection criteria for surgery or non-surgery are not established. Third, few specific treatments for elderly patients (EPs) are investigated. In conclusion, there are many reports about treatment of esophageal squamous cell carcinoma for EPs, although treatment strategy is still controversial. We have to consider well-designed prospective trial to confirm specific treatment strategy according to each stage.